Transition of Liesegang Precipitation Systems: Simulations with an Adaptive Grid PDE Method (Communications in Computational Physics, 2011)
The dynamics of the Liesegang type pattern formation is investigated in acentrally symmetric two-dimensional setup. According to the observations in real experiments,the qualitative change of the dynamics is exhibited for slightly differentinitial conditions. Two kinds of chemical mechanisms are studied; in both cases thepattern formation is described using a phase separation model including the Cahn-Hilliardequations. For the numerical simulations we make use of an adaptive gridPDE method, which successfully deals with the computationally critical cases such assteep gradients in the concentration distribution and investigation of long time behavior.The numerical simulations show a good agreement with the real experiments.